Rhino Orbital Mucormycosis in Post COVID-19 Patient - Alias Rathinam, J. Vadivazhagan; Habibunisha, H.; Nivethitha, K.; Chitra, Felicia (Innovational: Journal of Nursing and Healthcare, 2024)
Introduction: A case report of post of COVID-19 Rhino- orbital Mucormycois infection and its management. Presentation of Case: One case was diagnosed with COVID – 19 and treated according to the treatment regimen as per ICMR protocols following recovery the patient was discharged. Again the patient came with the complaints of swelling and pain with color changes in the left eye on the 12th day of discharge. Then, the diagnosis of mycormycosis was established after obtaining Computed tomography. Initially, the patient was treated with insulin therapy for control of blood glucose and also with Inj. Amphotericin B infusion along with routine other treatment. There was a progress in the severity of the signs and symptoms of Mucormycosis for the patient on discharge. Discussion: Mycormycosis generally develops due to comorbidity and immunosuppression. It mainly affects the head and neck, the head which has mainly the sinuses and connection of the respiratory system, further the head which consists of cranial structures and also visional tract. Hence, an early diagnosis and prompt treatment is needed for a good prognosis. Conclusion: Further, more research is needed to be carried out about opportunistic infections on COVID-19 regarding prevention, treatment modalities to reduce incidence and spread. There is a need for every organization to develop standard protocol according to ICMR guidelines for the treatment and control of this disease.